Crime prevention: approaches, practices, and evaluations - Lab, Steven P. (Routledge, 2016)
Preface -- Crime and the fear of crime -- Crime prevention -- Evaluation and crime prevention -- Primary prevention -- The physical environment and crime -- Neighborhood crime prevention -- Displacement and diffusion -- The mass media and crime prevention -- Developmental crime prevention -- General deterrence -- Secondary prevention -- Prediction for secondary prevention -- Situational crime prevention -- Partnerships for crime prevention -- Drugs, crime, and crime prevention -- The school and crime prevention -- Tertiary prevention -- Specific deterrence and incapacitation -- Rehabilitation -- Some closing thoughts on crime prevention and the future -- Glossary -- References -- Name index -- Subject index